GASTROPROTECTIVE ACTIVITY OF SESAME (SESAMUM INDICUM) SEEDS EXTRACT IN ALENDRONATE-INDUCED GASTRIC ULCER IN RATS - SHUBANGEE MISHRA; BALAJI O; VANISHREE RAO; SHALINI ADIGA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Bisphosphonates are known to cause gastritis and only few studies have evaluated the use of plant extracts in the treatment of bisphosphonate induced peptic ulcers. In the present study, we examined the effect of sesame seed extract in the alendronate-induced gastric ulcer in adult Wistar rats. Methods: Thirty adult Wistar rats (180–250 g) of both sexes, divided into five groups (n=6) were used: Group 1 (vehicle control) – 0.9% saline, Group 2 (ulcer control) – alendronate 60 mg/kg, Group 3 (standard) – alendronate 60 mg/kg + pantoprazole 30 mg/kg/day, Group 4 (test groups) – alendronate 60 mg/kg + sesame 0.5 mg/kg, and Group 5 (test groups) – alendronate 60 mg/kg + sesame 1 mg/kg. All drugs were given orally once daily for 7 days except for alendronate given only on day 1. On day 8, rats were sacrificed, and stomach tissues were analyzed macroscopically for ulcers. Estimation of gastric pH, acidity, and volume was done along with mucin content measurement. One-way ANOVA followed by Tukey’s post hoc test was used for statistical analysis with p<0.05 taken as significant. Results: Our study found that sesame extract given therapeutically at doses of 0.5 and 1 mg/kg showed comparable results with that of pantoprazole 30 mg/kg. Both the doses of sesame, 0.5 and 1 mg/kg showed similar gastroprotective activity against alendronate-induced gastric ulcers in Wistar rats. Conclusion: The findings of this study clearly demonstrated the protective effects of Sesame against alendronate-induced gastric ulceration.